Antecedents of Workplace Safety and Performance in Emergency Service Provider Company: An Empirical Investigation - J. Cheema, Luqman; Hussain, Nazia Munazer; Ishaq, Muhammad Ishtiaq; Asim, Ali Ijaz; Ullah, Abid (Archives of Business Research, 2014)
High Performance Work Practices (HPWP) is considered as best player to improve performance (financial and operational) and productivity. This notion is also proved by a meta-analysis conducted by Combs et al. (2006) by taking 92 studies accompanied by 19,319 organizations into considerations. However, the scant literature is available in Pakistani context especially in Emergency Service Provider Company. So, the current study explored the impact of ten HR practices (employee hiring, measurement, training, compensation, employee security, information sharing job quality, status distinction, decision making and transformational leadership) on workplace safety. Regression analyses was employed to test the study hypothesis and the results revealed that only three practices were found to be significant predictor of workplace safety and five dimensions for organizational performance. The implications and recommendations for future researchers were discussed hereunder. Key Words: Workplace Safety, High Performance Work Practices, Emergency Service Provider Company, Pakistan